Systemic Exercise-Induced Hypoalgesia Following Isometric Exercise Reduces Conditioned Pain Modulation. Issue 1 (3rd April 2018) - Alsouhibani, Ali; Vaegter, Henrik Bjarke; Hoeger Bement, Marie
Abstract: Objective: Physically active individuals show greater conditioned pain modulation (CPM) compared with less active individuals. Understanding the effects of acute exercise on CPM may allow for a more targeted use of exercise in the management of pain. This study investigated the effects of acute isometric exercise on CPM. In addition, the between-session and within-session reliability of CPM was investigated. Design: Experimental, randomized crossover study. Setting: Laboratory at Marquette University. Subjects: Thirty healthy adults (19.3±1.5 years, 15 males). Methods: Subjects underwent CPM testing before and after isometric exercise (knee extension, 30% maximum voluntary contraction for three minutes) and quiet rest in two separate experimental sessions. Pressure pain thresholds (PPTs) at the quadriceps and upper trapezius muscles were assessed before, during, and after ice water immersions. Results: PPTs increased during ice water immersion (i.e., CPM), and quadriceps PPT increased after exercise ( P  < 0.05). CPM decreased similarly following exercise and quiet rest ( P  > 0.05). CPM within-session reliability was fair to good (intraclass correlation coefficient [ICC] = 0.43–0.70), and the between-session reliability was poor (ICC = 0.20–0.35). Due to the variability in the systemic exercise-induced hypoalgesia (EIH) response, participants were divided into systemic EIH responders (N = 9) and nonresponders (N = 21). EIH responders experienced attenuated CPM following exercise ( P = 0.03), whereas the nonresponders showed no significant change ( P > 0.05). Conclusions: Isometric exercise decreased CPM in individuals who reported systemic EIH, suggesting activation of shared mechanisms between CPM and systemic EIH responses. These results may improve the understanding of increased pain after exercise in patients with chronic pain and potentially attenuated CPM.